ICT, global markets and small firms in less-developed regions in Europe - the case of mature sectors in a Spanish Province - Juan Carlos Rodríguez-Cohard; Encarnación Moral-Pajares (European Regional Science Association (ERSA), 2005)
Globalisation affects the smallest specialized companies in mature sectors, especially in the less developed regions in Europe. In these cases, the competitive advantage that these industries had achieved in the international market due to low costs of the factors has been broken. One way to improve its competitive position is an active participation in the international market through communication and information technologies along the productive chain. This paper describes these specialized companies in European mature sectors. Specially, we examine the of the province of Jaén (Andalusia). The results have been obtained surveying a hundred of companies –food, clothes and furniture sectors. These results show how these enterprises use communication and information technologies to adapt its competitive capacity in the new global market.
Keywords: 330